Good governance in rural development : country specif issues and experiences, proceedings of the COMSEC-BARD organized International Training Course on Good Governance in Rural Development 20 April - 02 May 2008 - International Training Course on Good Governance in Rural Development (2007 : BARD); Kashem, Mohammed Mir.; Karim, Abdul; Parvin Irin; 9; Commonwealth Secretariat (Dhaka : Bangladesh Academy for Rural Development, 2007)
Chiefly with reference to South Asia.
"Sponsored by Commonwealth Secretariat; organized by BARD"--Cover.
Includes bibliographical references.
Keywords: Rural development -- South Asia -- Congresses; Political participation -- South Asia -- Congresses